Peripheral blood mononuclear cell transplantation to treat no-option critical limb ischaemia: effectiveness and safety. (2nd July 2021) - Sermsathanasawadi, Nuttawut; Pruekprasert, Kanin; Chruewkamlow, Nuttapol; Kittisares, Kulvara; Warinpong, Thanatphak; Chinsakchai, Khamin; Wongwanit, Chumpol; Ruangsetakit, Chanean; Mutirangura, Pramook
Abstract : Objective: Local intramuscular transplantation of granulocyte colony-stimulating factor (G-CSF)-mobilised peripheral blood mononuclear cells (PB-MNC) has been shown to be effective for treating patients with no-option critical limb ischaemia (CLI) who are not considered suitable to undergo surgical bypass or percutaneous transluminal angioplasty. The aim of this study was to investigate the effectiveness and safety of PB-MNCs as a treatment for no-option CLI patients. Method: This prospective cohort study was conducted between April 2013 and December 2017. Patients with no-option CLI were treated with G-CSF 5–10 µg/kg/day for 3 days. PB-MNCs (7.1±2.2×10 10 ) with CD34+ cells (2.1±1.2×10 8 ) were collected by blood cell separator and then injected into the calf or thigh of ischaemic limbs. Ankle–brachial index, toe–brachial index and transcutaneous oxygen tension were recorded at 1 and 3 months after injection. The amputation rate and the wound healing rate were also recorded. Results: Eight patients took part in the study. Two patients experienced rest pain relief 1 month after PB-MNC therapy. Five patients had healed ulcer at 6 months after PB-MNC therapy. Limb ischaemia did not improve after PB-MNC therapy in one patient. Below-knee amputation was performed in that patient due to extension of gangrene. Two patients required reinjection of PB-MNCs because of recurrence of ischaemic ulcer. The limb salvage rate after 1 year was 87.5%. Conclusion: Local intramuscular transplantation of G-CSF-mobilised PB-MNCs might be a safe and effective treatment for no-option CLI patients.